Analisis Sistem Pengendalian Internal dan Audit Internal dalam Upaya Pencegahan Fraud (Kecurangan) - Windah Lestari; Sulaeman; Idang Nurodin (Universitas Muhammadiyah Surabaya, 2025)
Distribution industry in Indonesia faces major challenges in internal control due to operational complexity involving multi-channel distribution, supply chain management, and high cash flow. This study aims to analyze the performance of the internal control system in preventing fraud in distribution companies and identify gaps that have the potential to cause fraud. This research uses a descriptive qualitative method with a case study approach at PT. XYZ, a consumer goods distribution company that has many branches spread across Indonesia. Data collection techniques were conducted through in-depth interviews with several key informants and based on observations of distribution activities in the field. Secondary data was obtained from several campaigns and standard operating procedures (SOP). The results showed that the internal control system of PT XYZ has five main components according to the COSO framework, but its implementation is still not optimal. The research identified several fraud gaps that could potentially harm the company such as unlimited system access for some users, weak supervision during the consignment store stock-taking process, and lack of separation between work and social relationships in several divisions.The study recommends the implementation of a technology-integrated internal control system, strengthening the real-time monitoring system, establishing an independent internal audit unit, and developing an anti-fraud culture through continuous education programs.